Social Comparison and Optimal Contracts in the Competition for Managerial Talent - Anna Ulrichshofer; Markus Walzl (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2020)
We analyze the impact of social comparison on optimal contract design under imperfect labor market competition for managerial talent. Adding a disutility of social comparison as induced by a ranking of verifiable efforts to the multi-task model by Bénabou and Tirole (4238), we demonstrate that rankings can reduce welfare distortions of optimal screening contracts if the degree of competition for talent is sufficiently low. In contrast, a ranking unambiguously reduces welfare if the competition intensity is high and agents suffer from lagging behind while it can enhance welfare (depending on the fraction of high and low productivity types) if agents suffer from leading in a ranking (e.g., because the ranked activity is perceived as a substitute for other potentially pro-social activities).
Keywords: D02; D21; D43; D86; D91; G35; G41; J33; J41; 330; Incentive compensation; screening; imperfect labor market competition; socialcomparison; rankings